Oncogenic Intra-p53 Family Member Interactions in Human Cancers - Ferraiuolo, Maria; Di Agostino, Silvia; Blandino, Giovanni; Strano, Sabrina (Frontiers in Oncology, 2016)
The p53 gene family members p53, p73 and p63 display several isoforms derived from the presence of internal promoters and alternative splicing events. They are structural homologues but hold peculiar functional properties. p53, p73 and p63 are tumor suppressor genes that promote differentiation, senescence and apoptosis. p53, unlike p73 and p63, is frequently mutated in cancer often displaying oncogenic “gain of function” (GOF) activities correlated with the induction of proliferation, invasion, chemoresistance and genomic instability in cancer cells. These oncogenic functions are promoted either by the aberrant transcriptional cooperation of mutant p53 (mutp53) with transcription cofactors (e.g., NF-Y, E2F1, Vitamin D Receptor (VDR), Ets-1, NF-kB and YAP) or by the interaction with the p53 family members, p73 and p63, determining their functional inactivation. The instauration of these aberrant transcriptional networks leads to increased cell growth, low activation of DNA damage response pathways (DNA damage response (DDR), DNA double-strand breaks (DSBs) response), enhanced invasion and high chemoresistance to different conventional chemotherapeutic treatments. Several studies have clearly shown that different cancers harboring mutant p53 proteins exhibit a poor prognosis when compared to those carrying wild type p53 (wt-p53) protein. The interference of mutantp53/p73 and/or mutantp53/p63 interactions, thereby restoring p53, p73 and p63 tumor suppression functions, could be among the potential therapeutic strategies for the treatment of mutant p53 human cancers.